Removal of Nutrients From Anaerobically Digested Swine Wastewater Using an Intermittent Cycle Extended Aeration System - Dan, Nguyen Hong; Rene, Eldon R.; Le Luu, Tran (Frontiers in Microbiology, 2020)
Swine wastewater contains high concentrations of organic compounds, nutrients (nitrogen and phosphorus), heavy metals, and residual antibiotics, amongst others, that have negative impacts on the water environment. The main aim of this work was to remove nutrients from anaerobically digested swine wastewater using an intermittent cycle extended aeration system (ICEAS). The effects of operational parameters such as cycle time, organic loading rate, C/N ratio, and aeration/mixing ratio on the pollutant removal efficiencies of ICEAS were studied and compared with the performance of a conventional sequencing batch reactor (SBR). The following optimal conditions were obtained: cycle time, 6 h; organic loading rate, 0.86 kg COD m−3 day−1; C/N ratio, 2.49–2.82; and aeration/mixing ratio, 1.57. The pH was maintained in the range of 6.0–8.0. The total organic carbon (TOC), total nitrogen (TN), ammonium (NH4+), total phosphorus (TP), and color removal efficiencies of ICEAS were higher than those of the conventional SBR, with removal efficiencies of 95.22, 88.29, 97.69, 85.81, and 97.84%, respectively, compared to 94.34, 81.16, 94.15, 77.94, and 96.95%, respectively, observed in the SBR. TOC, TN, NH4+, TP, and the color removal efficiencies of ICEAS were higher by 0.88, 7.13, 3.54, 7.87, and 0.95%, respectively, than the conventional SBR. The good results from this study show that ICEAS is a promising technology for the removal of organic contaminants and nutrients from anaerobically digested swine wastewater and that the effluent water quality meets the Vietnamese discharge standard (QCVN 62-MT:2016/BTNMT) for swine wastewater effluents.